Mirror symmetry and Langlands duality in the non-Abelian Hodge theory of a curve - Hausel, T (2004)
This is a survey of results and conjectures on mirror symmetry phenomena in the non-Abelian Hodge theory of a curve. We start with the conjecture of Hausel-Thaddeus which claims that certain Hodge numbers of moduli spaces of flat SL(n,C) and PGL(n,C)-connections on a smooth projective algebraic curve agree. We then change our point of view in the non-Abelian Hodge theory of the curve, and concentrate on the SL(n,C) and PGL(n,C) character varieties of the curve. Here we discuss a recent conjecture of Hausel-Rodriguez-Villegas which claims, analogously to the above conjecture, that certain Hodge numbers of these character varieties also agree. We explain that for Hodge numbers of character varieties one can use arithmetic methods, and thus we end up explicitly calculating, in terms of Verlinde-type formulas, the number of representations of the fundamental group into the finite groups SL(n,F_q) and PGL(n,F_q), by using the character tables of these finite groups of Lie type. Finally we explain a conjecture which enhances the previous result, and gives a simple formula for the mixed Hodge polynomials, and in particular for the Poincare polynomials of these character varieties, and detail the relationship to results of Hitchin, Gothen, Garsia-Haiman and Earl-Kirwan. One consequence of this conjecture is a curious Poincare duality type of symmetry, which leads to a conjecture, similar to Faber's conjecture on the moduli space of curves, about a strong Hard Lefschetz theorem for the character variety, which can be considered as a generalization of both the Alvis-Curtis duality in the representation theory of finite groups of Lie type and a recent result of the author on the quaternionic geometry of matroids.